REGULASI EMOSI DAN KEMAMPUAN MEMECAHKAN MASALAH PADA IBU BEKERJA - May Neli; Indriyati Eko Purwaningsih (JURNAL SPIRITS, 2012)
ABSTRACTThe objective of this research is to identify the relationship between emotion regulation and problem-solving ability of working mother. The subject of the research is mothers working at UD Glouve Mandiri. The method of research employed is persons product-moment correlation method with purposive sampling technique.The data are collected using the scale of Anderson's Problem-Solving Ability and Emotion Regulation (Suharnan, 2005). Scale of Problem-Solving Ability consists of 31 items, whereas the scale ofEmotion Regulation consists of 42 items.The result of the research shows 0,437 correlation coefficient and 0,000 (p, < 0,05) significance level. This means that the hypothesis stating that there is a positive relationship between Problem-Solving Ability and Emotion Regulation is acceptable. The effectiveness of regression is 19,1%, which means that 19,1% of the Emotion Regulation is determined by Problem-Solving Ability and 80,9% is influenced by other factors.Key words: Emotion Regulation, Problem-Solving Ability